2003
DOI: 10.4049/jimmunol.171.7.3823
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines Regulate the Pattern of Rejection and Susceptibility to Cyclosporine Therapy in Different Mouse Recipient Strains After Cardiac Allografting

Abstract: We determined the role of cytokines in regulating the pattern of rejection and recipient susceptibility to cyclosporine (CsA) in a mouse cardiac allograft model. Hearts from C3H mice transplanted into untreated BALB/c (Th2-dominant) and C57BL/6 (Th1-dominant) mice showed different patterns of rejection. C3H allografts in BALB/c mice showed typical acute vascular rejection (AVR) with strong intragraft deposition and high serum levels of anti-donor IgG with predominant IgG1, while C3H allografts in C57BL/6 mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
47
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 43 publications
8
47
0
1
Order By: Relevance
“…We previously reported that C3H mouse hearts transplanted into BALB/c mice developed typical features of AVR (37,41). To determine whether bone grafting can prevent AVR, we took advantage of this model to study the ability of bone grafting alone or in combination with CsA to inhibit the humoral immune response against the allograft.…”
Section: Long-term Surviving Recipients Receiving Bone Grafting and Cmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously reported that C3H mouse hearts transplanted into BALB/c mice developed typical features of AVR (37,41). To determine whether bone grafting can prevent AVR, we took advantage of this model to study the ability of bone grafting alone or in combination with CsA to inhibit the humoral immune response against the allograft.…”
Section: Long-term Surviving Recipients Receiving Bone Grafting and Cmentioning
confidence: 99%
“…At necropsy, heart tissue samples were fixed in 10% buffered formaldehyde, embedded in paraffin, and sectioned at 5 m for H&E staining (37). The microscopic sections were examined in a blinded fashion for severity of rejection by a pathologist (B.G.).…”
Section: Graft Histologymentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike allografts, Th1 cytokines such as IFN-␥ and IL-12 are beneficial to xenograft survival because of their negative effect on AVR. In recent findings, we demonstrated that distinct cytokine profiles expressed by different mouse strains played an essential role in regulating the pattern of rejection and outcome of cyclosporin A (CsA)/rapamycin therapy in allotransplantation (2). These data suggest that the cytokine profile appears to be a key factor in determining the pattern of rejection and susceptibility to immunosuppressive agents.…”
mentioning
confidence: 97%